Molecular mechanisms of resistance to therapeutic MEK inhibition in BRAF [V600E] cancer - Dorris, Emma R. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2013)
Aberrant activation of the mitogen activated protein kinase (MAPK) pathway is common in solid tumours. This hierarchical pathway consists of a three-tiered kinase casade of BRAF, MAPK kinase (MEK1/2) and the extracellular signal-regulated kinase (ERK1/2). Extracellular ligands activate the pathway by binding to receptors on the cell surface that signal through the small GTRase RAS to recruit and activate BRAF, which initiates a kinase cascade through MEK1/2 and ERK1/2 to activate downstream transcription factors involved in a range of biochemical processes including differentiation, proliferation, growth and survival. Mutations in BRAF occur at an estimated rate of 50-80% melanoma and 45% in thyroid carcinoma. The most common BRAF mutation is a single base pair change, T1799A, that results in a valine to glutamic acid change at position 600 in the BRAF polypeptide (BRAF V600E). This causes a conformational change in the BRAF protein leading to constitutive activation and oncogene addiction to the MAPK pathway.
Keywords: Molecular Medicine, Ph.D.; Ph.D. Trinity College Dublin